Students’ Perception and Writing Competence towards the Use of Google Classroom in Learning Writing - Wicaksono, Rachmad Agung (RETAIN, 2021)
The purpose of this study was to describe the perception and writing competence of tertiary level students towards the use of Google classroom in learning academic writing course namely analytical and expository writing. There were fifteen participants in this study consisted of undergraduate students of certain university in Surabaya, Indonesia. In order to describe their perception, questionnaires and semi-structured interview were given. While, their writing competencies were analyzed using a writing rubric. The result of this study showed that 67% of the students showed excellent perception, 27% have good perception, and 7% have fair perception. Thus, the students showed overall excellent perception towards the use of Google classroom in analytical and expository writing course. Furthermore, 67% of the students showed excellent writing competence, 27% showed adequate competence, and the remaining 7% showed fair competence. Thus, it can be inferred that students’ writing competences in analytical and expository writing course are considered excellent. Keywords: Google classroom, Students’ perception, Writing competence